Application of Construal-Level Theory to Promotional Strategies in the Hotel Industry. (March 2016) - Kim, Jungkeun; Kim, Peter BeomCheol; Kim, Jae-Eun; Magnini, Vincent P.
Effectively promoting products and services is important for the success of tourism companies in the competitive business environment. Based on construal level theory, this study examines whether psychological distance (temporal and spatial) influences preferred promotional messages in the tourism industry. The results from three experimental studies indicate that people who plan a vacation in the distant-future/to a far-destination prefer abstract promotional messages, while those who plan in the near-future/to a near-destination prefer concrete ones. We also find that informational media (textual vs. pictorial) have significant influences regarding the impact of psychological distance on travelers' preferred promotional information. Further, using a field study, we investigate whether the current advertisements produced by tourism organizations are properly designed to be congruent with spatially driven construal levels (e.g., concrete promotional information for a near destination) but find them incongruent with what this study suggests. Implications of the findings are discussed for both researchers and practitioners.